Characterization of triboelectrically charged particles deposited on dielectric surfaces - Nesterov-Müller, Alexander; Löffler, F.; Cheng, Yun-Chien; Torralba, Gloria Collados; König, Kristina; Hausmann, Michael; Lindenstruth, Volker; Stadler, Volker; Bischoff, F. Ralf; Breitling, F. (Journal of physics. D, Applied physics, 2010)
A device for the measurement of q/m-values and charge degradation of triboelectrically charged particles deposited on a surface was developed. The setup is based on the integration of currents, which are induced in a Faraday cage by insertion of a solid support covered with charged particles. The conductivity of different particle supports was taken into account. The ‘blow-off’ method, in which the particles are first deposited, and then blown off using an air stream, can be used for characterization of triboelectric properties of particles relative to different surfaces.
Gesehen am 10.05.2023